Features of orthodontic treatment of patients with generalized periodontitis - Batih Ірина Вікторівна; Borysenko Анатолій Васильович (Actual Dentistry, 2023)
Summary. The need for orthodontic treatment in patients with generalized periodontitis is unquestionable today. However, in the case of orthodontic treatment of patients with generalized periodontitis, it should be remembered that the orthodontic treatment itself can damage the periodontal tissues. This should be taken into account by periodontologists when choosing a method of orthodontic treatment. Taking into account these circumstances, the preparation "Kalcinova" was used to strengthen the bone mineralization of the alveolar process. Aim. To determine the effectiveness of orthodontic treatment of patients with generalized periodontitis using a drug to stimulate alveolar bone mineralization. Materials and methods. This study was conducted on a group of 36 patients with generalized periodontitis of a young age (18–35 years) with the absence of autonomic dysfunction - a state of eytonia. Patients underwent orthodontic treatment. To strengthen the processes of bone mineralization of the alveolar bone, the patients of the main subgroup were prescribed the drug "Kalcinova". All patients underwent a comprehensive examination of the periodontium with the determination of the necessary hygienic indices to assess the state of the periodontium during treatment. Results. The examination of patients with generalized periodontitis after carrying out appropriate measures of therapeutic treatment showed a significant improvement in the condition of periodontal tissues. The beneficial effect of orthodontic treatment and stimulation of alveolar bone mineralization on the periodontal condition of patients is shown. Certain dynamics of the pathological process under the influence of complex treatment have been established. Analysis of the obtained results confirms the need for orthodontic treatment of patients with generalized periodontitis using methods of bone mineralization stimulation. It is shown that their use increases the effectiveness of treatment of generalized periodontitis. Conclusions. The combination of orthodontic treatment and a drug that increases bone mineralization of the alveolar process significantly improves the periodontal condition of patients with generalized periodontitis. The effectiveness of the use of the drug "Kalcinova" for stimulating bone mineralization of the alveolar process of patients and maintaining the level of attachment is shown.